2008
DOI: 10.1056/nejmoa0801369
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Hypertension in Patients 80 Years of Age or Older

Abstract: Background Whether the treatment of patients with hypertension who are 80 years of age or older is beneficial is unclear. It has been suggested that antihypertensive therapy may reduce the risk of stroke, despite possibly increasing the risk of death. Methods We randomly assigned 3845 patients from Europe, China, Australasia, and Tunisia who were 80 years of age or older and had a sustained systolic blood pressure of 160 mm Hg or more to receive either the diuretic indapamide (sustained release, 1.5 mg) or mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

38
1,629
3
202

Year Published

2009
2009
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 2,755 publications
(1,912 citation statements)
references
References 32 publications
38
1,629
3
202
Order By: Relevance
“…The age-related arterial hardening and aortic stiffness seen in many elderly hypertensive patients makes it more difficult to control the SBP component [1][2][3]23]. In this situation, physicians need to be educated that achieving BP goals is likely to require combination therapy with three or more antihypertensive drugs, given the likely multifactorial origin of the hypertension [1,24,25].…”
Section: Discussionmentioning
confidence: 99%
“…The age-related arterial hardening and aortic stiffness seen in many elderly hypertensive patients makes it more difficult to control the SBP component [1][2][3]23]. In this situation, physicians need to be educated that achieving BP goals is likely to require combination therapy with three or more antihypertensive drugs, given the likely multifactorial origin of the hypertension [1,24,25].…”
Section: Discussionmentioning
confidence: 99%
“…25 In addition, the HYVET (Hypertension in the Very Elderly Trial) study has also shown that treating hypertension reduces the risk of death from stroke, and from any cause in very elderly patients (aged 480 years). 26 Of further relevance here is a recent analysis that looked at patients in this study who received olmesartan/ amlodipine 40/5 mg or 40/10 mg during the final open-label phase. This found that baseline SeSBP was related to the change in SeSBP achieved at the end of the study, so that patients with higher baseline levels of SeSBP showed larger reductions.…”
Section: Discussionmentioning
confidence: 99%
“…1 Achieving blood pressure control (BP) in patients with hypertension reduces the risk of stroke and ischemic heart disease. [2][3][4] Despite everincreasing public health resources dedicated to improving BP control, [5][6][7] only half of the 78 million Americans with hypertension have their BP treated and controlled to the recommended value of below 140/90 mmHg. 8 Under new BP targets recommended by the Panel Members Appointed to the Eighth Joint National Committee (JNC 8), 9 BP is controlled in less than 60 % of hypertensive patients overall, and in less than 50 % of patients younger than 60 years of age.…”
Section: Introductionmentioning
confidence: 99%